A variação estilística na concordância nominal e verbal como construção de identidade social - Salomão-Conchalo, Mircia Hermenegildo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Putting into question the theoretical status of the variable rule in the mid-80s, Eckert (2000) brought in a new trend in sociolinguistics when he proposed a new concept of variable rule, which now constitutes a privileged space of the construction of social language meaning. It is this theoretical model that this research adopted. Within this theoretical framework, the purpose of this study was to analyze the dynamics and social practices of two groups of students, ideologically opposed, from the same public school in the city of São José do Rio Preto. The variable processes of nominal and verbal agreement were analyzed as the identity construction of these social categories markers. In the survey, two groups of high school students, divided into two opposing social classes, called funkers and eclectics, were followed for two years in ethnographic research. On one hand, the group of funkers is formed by teenagers who do not give much value to their educational institution and who identify themselves with hip hop, funk and rap culture. On the other hand, members of the eclectic group, opposites ideologically, like going to school and doing extracurricular activities, such as language courses, and they have a greater focus on higher education in the future; furthermore, these students circulate among the other school groups and generally are able to live with the differences between them; it is for this reason they call themselves eclectics. The purpose of this research was to investigate how these students construct their linguistic and social identity through their social practices and their symbolic relationships. In order to follow these two communities of practice, the qualitative and quantitative research was adopted. The qualitative analysis was ethnographic and the research was characterized by a direct contact of the researcher with the investigated situation, in which relationships were established day by day ...

Pondo em xeque o estatuto teórico da regra variável em meados dos anos 80, Eckert (2000) inaugurou uma nova tendência na Sociolinguística ao propor um novo conceito de regra variável, que passa a constituir espaço privilegiado da construção do significado social da linguagem. É esse modelo teórico que esta pesquisa adotou. No âmbito desse quadro teórico, o objetivo deste trabalho foi o de analisar as dinâmicas e as práticas sociais de dois grupos de estudantes, ideologicamente opostos, de uma mesma escola pública da cidade de São José do Rio Preto, e observar se os processos variáveis de concordância verbal e nominal poderiam ser marcadores de construção de identidade dessas categorias sociais. Na pesquisa, dois grupos de alunos do Ensino Médio, divididos em duas categorias sociais opostas, denominados funkeiros e ecléticos, foram acompanhados por dois anos numa pesquisa de caráter etnográfico. O grupo dos funkeiros é formado por adolescentes que não dão muito valor a instituição de ensino e que se identificam com a cultura do hip hop, funk e rap. Já os membros do grupo dos ecléticos, opostos ideologicamente, gostam de frequentar a escola e de fazerem atividades extracurriculares como cursos de idiomas, além disso, têm uma preocupação maior com o ensino superior no futuro; circulam entre os outros grupos da escola e, de modo geral, conseguem conviver com as diferenças entre eles; é por essa razão que assim se autodenominam. A finalidade desta pesquisa foi verificar como esses estudantes constroem a sua identidade linguística e social por meio de suas práticas sociais e de suas relações simbólicas. Para acompanhar essas duas comunidades de prática, adotou-se a pesquisa qualitativa e a quantitativa. A análise qualitativa, de base etnográfica, foi caracterizada por um contato direto do pesquisador com a situação investigada, onde se constroem as relações cotidianas; desenvolveu-se com base nos...
The stylistic variation on nominal and verb agreement as construction of social identity
Keywords: Linguistics; Linguística; Sociolinguística; Análise linguística (Linguística); Língua portuguesa - Variação; Lingua portuguesa - Estilo; Identidade social - São José do Rio Preto (SP)